2012
DOI: 10.3389/fpsyg.2012.00005
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Asymmetries: The Comparative View

Abstract: Hemispheric asymmetries play an important role in almost all cognitive functions. For more than a century, they were considered to be uniquely human but now an increasing number of findings in all vertebrate classes make it likely that we inherited our asymmetries from common ancestors. Thus, studying animal models could provide unique insights into the mechanisms of lateralization. We outline three such avenues of research by providing an overview of experiments on left–right differences in the connectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 103 publications
3
94
0
Order By: Relevance
“…Interestingly, communication asymmetry has been reported in bats at the level of single cortical neurons, with left-hemispheric neuronal advantage for processing social calls and right-hemispheric neuronal advantage in processing navigational signals [24]. These findings including the present results suggest a phylogenetically early emergence of vocal communication asymmetries [4]. Accordingly, language lateralization in humans may reflect a more primitive left-hemispheric dominance for processing basic features of species-typical sounds [16] in which temporal features might be determinant auditory cues for call recognition.…”
Section: Rea As a Mechanism For Processing Acoustic Stimulisupporting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, communication asymmetry has been reported in bats at the level of single cortical neurons, with left-hemispheric neuronal advantage for processing social calls and right-hemispheric neuronal advantage in processing navigational signals [24]. These findings including the present results suggest a phylogenetically early emergence of vocal communication asymmetries [4]. Accordingly, language lateralization in humans may reflect a more primitive left-hemispheric dominance for processing basic features of species-typical sounds [16] in which temporal features might be determinant auditory cues for call recognition.…”
Section: Rea As a Mechanism For Processing Acoustic Stimulisupporting
confidence: 73%
“…lateralization or asymmetry of brain function, has been described in many vertebrate taxa including fish, frogs, reptiles, birds and mammals [1][2][3], as a fundamental aspect of nervous system organization [4]. The left hemisphere is specialized to categorize information and responds to features that are invariant and repeated, while the right domestic horses [18] and rhesus macaques [19].…”
Section: Introductionmentioning
confidence: 99%
“…A similar complex architecture has been reported in human and other fish handedness and brain lateralization (reviewed in Ocklenburg & Gunturkun, 2012). …”
Section: Discussionsupporting
confidence: 74%
“…I agree with Ocklenburg and Güntürkün (2012) (Hynd et al, 1995), white matter constitutes a perfect mirror candidate of the developmental nature of human language acquisition. Besides, as I noted above, the chemical mechanisms of myelination are decisive for axons' generating action potentials, something that can be directly associated with the oscillatory basis of language I will shortly highlight.…”
Section: Brain Asymmetry -Lateralizationmentioning
confidence: 91%
“…Comparative studies have suggested a left-hemispheric dominance for conspecific communication in a wide variety of species (Ocklenburg and Güntürkün, 2012), such as chimpanzees (Taglialatela et al, 2008), rhesus monkeys (Hauser and Andersson, 1994), dogs (Siniscalchi et al, 2008), mice (Ehret, 1987), sea lions (Böye et al, 2005), and frogs (Bauer, 1993). More tellingly, a left-dominance has been reported in canaries as regards to hypoglossal functions (Nottebohm, 1971), in zebra finches concerning vocal learning (Voss et al, 2007; and in Bengalese finches for song discrimination (Okanoya et al, 2001).…”
Section: Brain Asymmetry -Lateralizationmentioning
confidence: 98%